The Pengaruh Pengungkapan Environmental, Social, Governance terhadap Kinerja Keuangan - Putra, Gede Sanjaya Adi; Damaryanti, Ni Kadek; Dewi, Kadek Goldina Puteri (Magister Ilmu Akuntansi Universitas Jambi, 2026)
This study aims to determine the effect of environmental, social, and governance disclosure on financial performance. The objects of this study are companies in the basic materials and energy sectors listed on the Indonesia Stock Exchange in 2024. Using purposive sampling, 64 data observations were obtained. The data used is secondary data obtained from sustainability reports and financial reports. Environmental, social, and governance disclosure uses GRI 2021 standard data, while financial performance is proxied by return on assets (ROA). Data analysis techniques use multiple linear regression analysis, using SPSS 25 software. Liquidity, measured using the current ratio (CR), was used as a control variable to control for the influence of internal company factors related to the ability to meet short-term obligations. The results showed that environmental disclosure had no significant effect on financial performance. Social disclosure had no significant effect on financial performance. Governance disclosure had a significant negative effect on financial performance.